THE IMPORTANCE OF STRENGTHENING NATIONAL IDENTITY IN EDUCATION TO MANAGE CHARACTER BUILDING IN THE ALPHA GENERATION - Syaqina, Dianita Widya; Mutsaqofah, Marsa Bila; Yohamintin, Yohamintin; Fadhilah, Hasna Khalishah; Nafasabilla, Zaskia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to determine the importance of strengthening national identity in education to manage character building in the alpha generation. This research uses a qualitative method with a case study approach in one of the public schools. The participants in this study amounted to 4 students and 8 teachers. Data analysis used an interactive model from Miles and Huberman through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that strengthening national identity in education has a positive impact on character building for the alpha generation. This can be seen from the increase in student characters such as being independent, caring for friends, being able to work together and also being able to respect and appreciate religious differences and manners that are increasing. These characters are formed through culture-based learning at school.